Brazilian men's volleyball: analysis of attacks carried out from the attack zone - De Conti Teixeira Costa, G.; Rodrigues Roca, A. C.; Ugrinowitsch, H.; Barreiros Freire, A.; De Oliveira Castro, H.; Moreira Praça, G.; Ferreira de Britto Evangelista, B. (Journal of Physical Education and Sport, 2019)
The present study aims to analyze the predictive factors of the effects of attacks carried out from the attack zone. The sample consisted of the observation of 8,059 attack actions of the Brazilian men`s Super League in 2014-2015. The variables analyzed were reception effect, attack tempo, and attack effect. The results showed that excellent reception, first attack tempo and powerful attacks increase the chance of scoring; defense of attack increases the chances of occurring after moderate reception but reduces them after first attack tempo and powerful attacks; attack blocked increases the chance of occurring after the powerful diagonal attack. In conclusion, in contemporary volleyball, the effect of the reception should be high to allow all options of attack to score, even attack with speed and attack with power, when the attack is performed from the attack zone.